Gas-phase infrared spectroscopy of glycans and glycoconjugates. (February 2022) - Greis, Kim; Kirschbaum, Carla; von Helden, Gert; Pagel, Kevin
Abstract: Glycans are intrinsically complex biomolecules that pose particular analytical challenges. Standard workflows for glycan analysis are based on mass spectrometry, often coupled with separation techniques such as liquid chromatography and ion mobility spectrometry. However, this approach does not yield direct structural information and cannot always distinguish between isomers. This gap might be filled in the future by gas-phase infrared spectroscopy, which has emerged as a promising structure-sensitive technique for glycan fingerprinting. This review highlights recent applications of gas-phase infrared spectroscopy for the analysis of synthetic and biological glycans and how they can be integrated into mass spectrometry-based workflows. Highlights: Gas-phase infrared (IR) ion spectroscopy is increasingly used for glycan analysis. Spectral libraries enable the structural assignment of glycans. In combination with computational chemistry, IR spectra reveal 3D structures. Analytical challenges differ between glycan classes. Technical developments aim at a broader availability of IR ion spectroscopy.